A Design for Additive Manufacturing approach based on process energy efficiency: Electron beam melted components. (25th March 2021) - Giudice, Fabio; Barbagallo, Raffaele; Fargione, Giovanna
Abstract: In the present paper a Design for Additive Manufacturing approach is proposed, with the aim to outline a generalized method and define an energy consumption model that allow, during the development of component design, to evaluate the effects of the different solutions on the energy efficiency of the additive process that will build the component. For this purpose the concept of building energy is introduced, that is the real energy of the heat source during the phases of the building process, and can be directly correlated to key properties of the component (material, geometry and shape, volumetric distribution). For the detailed formulation of the energy consumption model, the Electron Beam Melting technology has been considered. Two parameters are identified to effectively characterize each design solution, combining the geometric and volumetric properties of components in the most significant way, and taking into account also the efficiency in build volume packing. The application of the model to the fabrication of components characterized by different shape classes is detailed, highlighting how a different spatial distribution of the same volume affects the building energy. The outcomes in terms of energy consumption, due to alternative design choices, can be assessed and simulated. The analysis of critical points in the design solutions presents an heuristic potential, as it can guide the designer in effective improvement interventions. The accuracy in the evaluation of the process energy consumption due to the proposed approach, also suggest limiting the use of simplifications, that may not be fully suitable to correlate energy efficiency and component properties in a Design for Additive Manufacturing perspective. Highlights: Energy efficiency in additive process is correlated to component design parameters Energy consumption model is focused on beam energy used in building phases Parameters to characterize component by shape and packing properties are introduced Local and global analyses can improve energy efficiency of design solutions Different spatial distributions of the same volume affects energy consumption